Artificial‐Intelligence‐Enabled Reagent‐Free Imaging Hematology Analyzer. (24th August 2021) - Shu, Xin; Sansare, Sameera; Jin, Di; Zeng, Xiangxiang; Tong, Kai-Yu; Pandey, Rishikesh; Zhou, Renjie
Abstract : Quantitative Phase Imaging A reagent‐free hematology analyzer is developed in article number 2000277 by Rishikesh Pandey, Renjie Zhou, and co‐workers. The researchers employ a quantitative phase imaging in conjunction with a neural network to classify leukocytes. In the cover image, cells are illuminated by a laser and phase images are acquired by a custom‐built microscope (indicated by the objective lens). An AI algorithm (denoted by the background data flow) is used for classifying cells.